2023
DOI: 10.1002/jcla.24850
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterizations of antibiotic resistance, biofilm formation, and virulence determinants of Pseudomonas aeruginosa isolated from burn wound infection

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In an investigation conducted by Banar et al [9] investigated 55/ 57 (96.5%) strains of P. aeruginosa were www.minarjournal.com characterize by their capacity to produce biofilms and found 30.9%, 47.3%, and 21.8% of these isolates formed strong, moderate and weak biofilm layers, respectively. Ghasemian et al [23] also reported strong, medium and weak biofilm production of 42.5%, 35% and 22.5%, respectively. In this research, it was evident that there was a statistically significant association between MBLs and biofilms formation and these findings are in line with those of Heydari and Eftekhar [18] , Ghasemian et al [23] , and Singhai et al [24] .…”
Section: Discussionmentioning
confidence: 93%
“…In an investigation conducted by Banar et al [9] investigated 55/ 57 (96.5%) strains of P. aeruginosa were www.minarjournal.com characterize by their capacity to produce biofilms and found 30.9%, 47.3%, and 21.8% of these isolates formed strong, moderate and weak biofilm layers, respectively. Ghasemian et al [23] also reported strong, medium and weak biofilm production of 42.5%, 35% and 22.5%, respectively. In this research, it was evident that there was a statistically significant association between MBLs and biofilms formation and these findings are in line with those of Heydari and Eftekhar [18] , Ghasemian et al [23] , and Singhai et al [24] .…”
Section: Discussionmentioning
confidence: 93%
“…Infections by dangerous pathogens, such as Pseudomonas aeruginosa or Acinetobacter baumannii, delay patient recovery and can even lead to patient death [29]. This is partially due to an increased resistance to antibiotics which has been described in Pseudomonas aeruginosa and Acinetobacter baumanii in the context of burn wounds [30,31]. Wound infection, however, starts with colonization [32].…”
Section: Discussionmentioning
confidence: 99%
“…investigated the antibacterial potential. With a blade, cuts were made that later became infected with Pseudomonas aeruginosa strains [27]. The effects of chamomile and tetracycline ointments were then compared.…”
Section: Chamomilla Anti-microbial Activitymentioning
confidence: 99%